2013
DOI: 10.1590/s0034-737x2013000200020
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation, production and quality of coffee beans

Abstract: RESUMO Efeito do zinco na produção e qualidade dos grãos de caféApesar da importância do zinco na nutrição do cafeeiro, quase não há informações que relacionem o suprimento de zinco e a qualidade dos grãos. Este trabalho avaliou o efeito de zinco sobre a produção e a qualidade dos grãos de café. O experimento foi conduzido com Coffea arabica L. na Zona da Mata de Minas Gerais, Brasil. O delineamento utilizado foi inteiramente ao acaso, com dois tratamentos: suplementação com zinco (oito parcelas) e controle, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 10 publications
3
24
0
2
Order By: Relevance
“…Martinez et al [56] studying Zn effect on the production and cupping quality of coffee did not observe Zn effect on the coloration index, with the mean values being 0.95 DO 425 nm, which is in agreement with the results found by Lima et al [59] for good coffees and, also, with the means found in this work.…”
Section: Electrical Conductivity Leached Potassium and Coloration Isupporting
confidence: 93%
See 2 more Smart Citations
“…Martinez et al [56] studying Zn effect on the production and cupping quality of coffee did not observe Zn effect on the coloration index, with the mean values being 0.95 DO 425 nm, which is in agreement with the results found by Lima et al [59] for good coffees and, also, with the means found in this work.…”
Section: Electrical Conductivity Leached Potassium and Coloration Isupporting
confidence: 93%
“…In a field experiment performed in the same conditions of that of the experiment reported here, Martinez et al [56] studied the effect of Zn on the production and on some quality attributes of coffee beans and did not observe effect of the nutrient on the production; however, there was an effect of Zn on beans size. Moreover, plants supplemented with Zn had the highest percentage of exportable grains, retained in the sieves 17 and 18.…”
Section: Productionmentioning
confidence: 72%
See 1 more Smart Citation
“…The total titratable acidity (ATT) of coffee beans has an inverse relationship with the coffee beverage quality, because better quality coffees have lower total titratable acidity (Martinez, Poltronieri, Farah, & Perrone, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Neves et al, (2011) observaram que o fornecimento de Zn influenciou positivamente a produção e a qualidade dos grãos de café, caracterizada pelo seu tamanho, percentagem de grãos brocados, condutividade elétrica e o potássio lixiviado dos grãos. Os resultados de Martinez et al (2013) corroboraram os anteriores e indicaram, ainda, que os grãos de cafeeiros supridos com Zn apresentaram maiores teores de ácidos clorogênicos e maior atividade antioxidante.…”
Section: Boro Cobre E Zincounclassified